Teachers' belief and implementation of ICT in early childhood education classroom - Sulistyaningtyas, Reza Edwin; Astuti, Febru Puji; Yuliantoro, Prasetyo; Hidayaturrohman, Qisthi Alhazmi (Universitas Negeri Yogyakarta, 2024)
Technology has a vital role in every aspect of life. Early childhood education also requires technology in its learning. This study aims to analyze teacher beliefs and explain the application of ICT in Early Childhood Education (ECE) classes. This research uses mixed methods, questionnaires, and interviews as data collection tools. Questionnaires were used to obtain data related to ICT used in ECE and teacher beliefs, while interviews were used to obtain data on the implementation of ICT in ECE classrooms. The sample was 132 ECE teachers in Magelang, Central Java, and Yogyakarta. The sampling technique used is a simple random sampling technique. Regression analysis is used in this study's data analysis technique. The results obtained include 1) 40% of teachers use laptops in class, 2) 26.67% of teachers never involve children in using ICT, and 3) there is a relationship between educational background and ICT implementation beliefs in class. Implication This study aims to hold workshops for ECE teachers to apply ICT in learning activities involving children in their use.